The legacy of the reformasi: The role of local government spending on industrial development in a decentralized Indonesia - Bangkit A. Wiryawan; Christian Samen Otchia (Journal of Economic Structures, 2022)
Starting in 2001 the Government of Indonesia employed the Regional Autonomy Law, providing larger fiscal role to the province and district governments. However, our understanding of its impacts on development in Indonesia is still limited. This paper seeks to find the relationship between increasing local governments' capital expenditure and industrial development with focus in the non-oil and gas sector. Capital spending is thought to have moderation effect on investment, the main channel for industrialization, that should contribute to industrial growth. Our System GMM results suggest that there are positive and significant correlations between capital spending and industrial growth, presenting evidence of local governments' role. However, we fail to find significant moderation effect between local capital spending and industrial investment towards the sector's growth. This poses problem for industrialization at the local level. Decentralization progress in Indonesia has been institutionally anchored by the central government, particularly with the introduction of concurrent affairs in 2004 that allowed Jakarta to take a major developmental role in districts and provinces at the cost of lesser local governments' role. Our study proposes a new institutional model that promote better central-local collaboration.
Keywords: 330; Capital spending; Decentralization; Industrial development; Investment; Local government